The oversight role of the National Deprtment of Human Settlements on its entities: the case of NHBRC - Mgiba, Reineth Ngilishi (My University, 2012)
Research on the oversight role of the National Department of Human Settlements on its public entities: The case of National Home Builders Registration Council (NHBRC). This study looked at the National Department of Human Settlement’s oversight role over its entities. It took place in the context of broad departmental public entity oversight management. However, the researcher’s focus was on the systems and mechanisms used by the department in its oversight function with a specific focus on the National Home Builders Registration Council as one of its entities and determined if there were any impede oversight challenges. The research explored through documentary analysis and investigative interviews with departmental officials who are charged with the responsibility of overseeing the governance of all entities reporting to the NDoH. Key accountability documentation, and commentary documents from oversight organs of state such the Auditor General and Parliamentary Portfolio Committee on Human Settlements were also reviewed and analysed. 5 The research discovered that the department’s oversight over the NHBRC, is mainly focusing on compliance enforcement. The mechanisms and systems used are somewhat biased towards compliance monitoring. As a result of the skewed focus, there is an imbalance between legislative enforcement and service delivery on the part of NHBRC. Although the research could not make inferences to other public entities, the study helped in developing an understanding of challenges associated with oversight (generally) and the strength and weaknesses of the department’s oversight systems and mechanisms (in particular). The research unveiled a need for an improvement in regard to the oversight systems and approach, and concludes by recommending that it would be necessary that government should introduce a holistic oversight framework that would guide and promote efficiency and effectiveness in all “public entities oversight initiatives”.
Keywords: Legislative oversight; Local government; Housing; South Africa